The Marketing Strategy for Effective Public Library Services in the Accra Metropolis - Insaidoo, A.W.K.; Armah, Angelina Lily (Ghana Library Journal, 2002)
The paper looks at the potentials and strategic importance of the Accra Central Library to the provision of effective and efficient library and information services to’the public and institutions in Accra, and its inability to contribute effectively to the development and growth in education, industry, commerce, culture, tourism, soc-io-economic and political activities in Accra and nation-wide. The writers have analysed the acute problems and issues that have stalled the continuous process of effective service delivery and also proposed a new marketing strategy that seeks a holistic approach to arfdressthe nagging issues and the way forward for a better library and information service provision in the Accra Metropolis. To revamp library and information services, and attract financial and material support from the public, profit-making institutions and nongovernmental institutions the writers have called for a closer collaboration of Management of the Library and identifiable institutions, politicians and other stakeholders .